Brand Image Mediates the Relationship between Influencer Credibility and Purchase Decisions among Generation Z - Rahmawaty, Penny; Eka Purnama, Dewanti (Universitas Negeri Yogyakarta, 2025)
This study investigates the influence of influencer credibility on Azarine product purchase decisions among Generation Z, with brand image serving as a mediating variable. Specifically, the research aims to determine the direct and indirect effects of influencer attractiveness, expertise, and trustworthiness on purchase decisions. A quantitative approach was employed using a survey method, with data collected via questionnaires distributed to 200 Generation Z respondents in Yogyakarta who use Azarine products. The sample was determined using a purposive sampling technique. The analysis method used in this study was Partial Least Square (PLS). The results show that all three dimensions of influencer credibility positively and significantly influence both brand image and purchase decisions. Furthermore, brand image significantly mediates the relationship between each dimension of influencer credibility and purchase decisions. These findings highlight the importance of selecting credible influencers and maintaining a strong brand image to drive consumer behavior in the competitive skincare market